2004
DOI: 10.1590/s0102-86502004000600010
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da Casearia sylvestris no reparo ósseo com matriz óssea bovina desvitalizada em ratos

Abstract: Objetivo: Estudar o efeito do decocto 5% de Casearia sylvestris no reparo de defeito femoral preenchido com matriz óssea bovina desvitalizada. Métodos: Vinte e quatro ratos Wistar, machos e adultos foram distribuídos aleatoriamente em dois grupos com 12 animais. Defeitos femorais bilaterais, com 2mm de diâmetro, foram produzidos na diáfise femoral e preenchidos com matriz óssea bovina desvitalizada. O grupo experimento recebeu 1mL de decocto 5% de Casearia sylvestris, por gavagem, durante o período de seguimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
0
8
0
3
Order By: Relevance
“…In microscopic evaluations, Casearia sylvestris did not improve the cicatrization process (Table 3). Sassioto et al (2004) observed that the Casearia sylvestris decoction promoted chronological delay in bone reparation in rats, possibly owing to anti-inflammatory activity and reduction in the macrophage, fibroblast, and collagen fiber population at the wound site. Dry and irregular crusts were observed in the lesions treated with Schinus terebinthifolius, an effect attributed to the astringent action of tannins found in the plant (Degáspari et al 2005).…”
Section: Lipinski Et Al Afr J Tradit Complement Altern Med (2012) mentioning
confidence: 96%
See 1 more Smart Citation
“…In microscopic evaluations, Casearia sylvestris did not improve the cicatrization process (Table 3). Sassioto et al (2004) observed that the Casearia sylvestris decoction promoted chronological delay in bone reparation in rats, possibly owing to anti-inflammatory activity and reduction in the macrophage, fibroblast, and collagen fiber population at the wound site. Dry and irregular crusts were observed in the lesions treated with Schinus terebinthifolius, an effect attributed to the astringent action of tannins found in the plant (Degáspari et al 2005).…”
Section: Lipinski Et Al Afr J Tradit Complement Altern Med (2012) mentioning
confidence: 96%
“…Casearia sylvestris has numerous pharmacological applications in human and dental health. Casearia sylvestris extracts exhibit anti-diarrhea, anti-thermal, depurative, anti-rheumatism, cicatrizing, and anti-inflammatory activities, and are also used for the treatment of snake bites (Sassioto et al, 2004;Arantes et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Decoction of C. sylvestris leaves was capable to decrease bone formation possibly because of the presence of anti-inflammatory phytochemical compounds and prostaglandin synthesis inhibition, which may cause inability in macrophage chemotaxis, fibroblast activation and collagen fiber arrangement and formation, with noticeable inhibitory effects on osteogenesis (Sassioto et al 2004). …”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…However, this has been seen to produce a severe inflammatory reaction (3,4,8,12,18,25,(33)(34)(35) . use of this type of material, in association with culturing of mesenchymal cells in order to boost their growth potential, seems to be the future of new advances (1,7,8,12,24,(32)(33)(34)(35) . Sugarcane biopolymer has already been used experimentally as a substitute for other tissues, in a support device for urinary incontinence (36) , as a replacement for vascular prostheses (23,37) , as a coadjuvant in wound healing (20) , as a replacement for the tympanic membrane (22) , in repairs to the dura mater (38) and in bladder tissue (39) .…”
Section: Discussionmentioning
confidence: 99%
“…Because chondrocytes are not vascularized, they do not form hematomas, fibrins or coagulum when injured, and they serve only as a framework for new repair tissue. The absence of a vascular phase limits the number of cells available for an inflammatory response to the trauma (1,(3)(4)(5)(6)(7)(8) . Among the treatments for repairing osteochondral defects, debridement of the injured cartilage,…”
Section: Introductionmentioning
confidence: 99%